Capsulotomy opening diameter outcomes in aphakic eyes after primary congenital cataract removal and its association - Zhao, Qihui; Chang, Pingjun; Zhao, Yinying; Wang, Dandan; Zhao, Yune (Frontiers in Pediatrics, 2023)
Aim: To observe the change of capsulotomy opening diameter (COD) in aphakic eyes after primary congenital cataract removal and investigate its influencing factors. Methods: Ocular parameters, including corneal diameter (CD), axial length (AL), anterior and posterior COD (ACOD, PCOD), and age at surgery were recorded at primary congenital cataract removal and secondary intraocular lens implantation. The concentrations of 15 kinds of cytokines in aqueous humor samples collected at the primary surgery were detected. The change (Δ) of COD between two surgeries were described, and its association was analyzed. Results: Fifty eyes from 33 patients with congenital cataract who underwent primary and secondary surgery were enrolled. The changes in ACOD and PCOD were not statistically significant on the whole. ΔACOD was positively correlated with ΔCD and the concentrations of PDGF-AA, VEGF and TGF-β1. The concentration of FGF-2 and the interval between two surgeries showed negative correlations with ΔACOD and ΔPCOD. Conclusion: COD in aphakic eyes kept changing after primary surgery. The positive correlation between ΔACOD and ΔCD manifested the enlargement of ACOD was influenced by lateral eye growth. Meanwhile, ΔACOD was also associated with cytokines, indicating postoperative inflammation promoted the ACOD constriction.